Learning path : functional programming for PHP 7 developers. - Bierer, Doug; Atencio, Luis; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"PHP 7 offers new features and tools to write optimized code. Functional programming is one such tool. If you're a PHP developer looking at enhancing your skills by working on over 80 real-world tasks and learning functioning programming, this Learning Path is for you. This Learning Path will start by demonstrating intermediate to advanced PHP techniques. You'll learn to solve practical, real-world problems faced by PHP developers like yourself every day. Then, you'll learn how to think about coding problems in terms of the composition of pure functions. The goal is to equip you to perform efficient coding in PHP 7."--Resource description page.
PHP 7 programming solutions / Doug Bierer -- Functional PHP 7 / Luis Atencio.
Presenters, Doug Bierer, Luis Atencio.
Title and publication information from resource description page (Safari, viewed March 8, 2017).
Keywords: PHP (Computer program language); Web site development; Electronic books